Comparative Study of Criminal Liability of Offenders Committing Fraud and Money Laundering Together as Continuing Actions - Faedonajokho Sarumaha; Selamat Lumban Gaol; Sujono (GoAcademica Research & Publishing, 2023)
The rapid progress in all areas of life including economic, financial, trade, banking and social developments has brought certain legal implications for Indonesia. Law plays an important role in human life, legal ties connect humans with other humans and connect humans with the objects around them. This type of research is normative legal research, namely legal research conducted by examining literature or secondary data which is also known as doctrinal research. The legal research approach is the statutory approach, case approach, conceptual approach. The statutory approach by examining all laws and regulations that are related to criminal issues of additional restitution for victims of criminal acts. First Anugerah Karya Wisata (First Travel). Furthermore, in the Decision of the Makasar District Court Number 1235/Pid.B/2018/PN.MKS in the case of money laundering and embezzlement, the regulation of criminal acts of jointly committing fraud and money laundering as continuing actions in criminal law in Indonesia is regulated by Article 3 Jo. Article 4 Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes (UU PP-TPPU). While the laws and regulations governing criminal acts of fraud are regulated in Article 378 of the Criminal Code.